Yolk sac tumor in children and the resulting biopsychosocial and spiritual aspects - Hidayatullah; Savitri, Irma; Lisal, Lenny M. (International Journal of Research in Medical Sciences, 2024)
Yolk sac tumor is a rare germ cell tumor in children, accounting for only about 3.5% of pediatric cancers. However, the yolk sac tumor is a malignant tumor that requires chemotherapy, but the side effects of chemotherapy can have an impact on the biopsychosocial and spiritual aspects of the child. This case report presents the negative impacts on the biopsychosocial and spiritual aspects of a child diagnosed with a yolk sac tumor. 11-year-old girl experienced symptoms of an enlarged abdomen, feeling bloated, pain, and frequent urination. The pathological examination revealed a yolk sac tumor, and the examination of ascites showed malignant cells. The patient was diagnosed with a yolk sac tumor, Stage 1C3, and was to undergo chemotherapy. She scored 15, indicating that the patient experienced anxiety due to the yolk sac tumor diagnosis and was anxious about the side effects of chemotherapy. Examination of the biological, psychological, social, and spiritual aspects in pediatric patients with a yolk sac tumor can assist in addressing the adverse effects of the diagnosis and the anxiety about chemotherapy in a more comprehensive manner.